CTLA4 blockade broadens the peripheral T cell receptor repertoire - Robert, Lidia (2014)
PURPOSE: To evaluate the immunomodulatory effects of CTLA-4 blockade with tremelimumab in peripheral blood mononuclear cells (PBMC). EXPERIMENTAL DESIGN: We used next generation sequencing to study the complementarity determining region 3 (CDR3) from the rearranged T cell receptor (TCR) variable beta (V-beta) in PBMC of 21 patients, at baseline and 30–60 days after receiving tremelimumab. RESULTS: After receiving tremelimumab there was a median of 30% increase in unique productive sequences of TCR V-beta CDR3 in 19 out of 21 patients, and a median decrease of 30% in only 2 out of 21 patients. These changes were significant for richness (p=0.01) and for Shannon index diversity (p=0.04). In comparison, serially collected PBMC from four healthy donors did not show a significant change in TCR V-beta CDR3 diversity over one year. There was a significant difference in the total unique productive TCR V-beta CDR3 sequences between patients experiencing toxicity with tremelimumab compared to patients without toxicity (p=0.05). No relevant differences were noted between clinical responders and non-responders. CONCLUSIONS: CTLA4 blockade with tremelimumab diversifies the peripheral T cell pool, representing a pharmacodynamic effect of how this class of antibodies modulates the human immune system.